STUDENTS’ COMPETENCE IN INTERPRETING DEIXIS IN DESCRIPTIVE TEXT ON PRAGMATICS COURSE OF ENGLISH LETTERS DEPARTMENTS OF UNIVERSITAS AHMAD DAHLAN IN 2017/2018 - Garda Arif Wicaksono (Jurnal Penelitian Humaniora, 2019)
This research is aimed to investigate the students’ competences in interpreting deixis in descriptive texts on pragmatics course and to find out the students’ difficulties in interpreting the types of deixis.This research uses quantitative research which is conducted on the students who take pragmatics course in English Letters Department of Universitas Ahmad Dahlan. The data are taken through a test. The instrument of test validity was assessed by the experts. The test is used to measure the students’ competence in interpreting deixis. To measure the reliability, this research uses Alpha formula. The data are analyzed using descriptive statistics.Based on the research finding, it can be concluded that the students’ competence in interpreting deixis in descriptive text is good to excellent. The result can be concluded as follows; (1) person deixis is good (50%); (2) time deixis is excellent (55%); (3) discourse deixis is excellent (45%); (4) social deixis is excellent (55%), and (5) place deixis is good (55%). The most mistakes which are done by students in interpreting deixis occur in discourse deixis. The cause of them can be; (a) having limited vocabularies; (b) less understanding the context of descriptive text; (c) difficult to comprehend the situational information in the descriptive text.